2021
DOI: 10.3390/su13116434
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Education Using Augmented Reality in Vocational Certification Courses

Abstract: In the field of vocational education, no studies have examined the use of augmented reality (AR) learning technologies in the teaching of cosmetology. However, this study proposed the “Makeup AR” learning approach and conducted a quasi-experiment to examine the interaction effect between said approach and students with active and reflective learning styles. The research participants were 70 students from a vocational senior high school. The experimental group comprised 36 participants who were taught using Mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 66 publications
0
12
1
Order By: Relevance
“…Many previous studies that utilized AR technology reported significant differences between the control and experimental groups [16,21]. Although the between-group statistical results did not show significant differences in this study, the experimental group did show more improvement in terms of the oyster knowledge test scores than the control group.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Many previous studies that utilized AR technology reported significant differences between the control and experimental groups [16,21]. Although the between-group statistical results did not show significant differences in this study, the experimental group did show more improvement in terms of the oyster knowledge test scores than the control group.…”
Section: Discussioncontrasting
confidence: 83%
“…AR is a computer graphic technology in which 3D virtual objects are immediately integrated into a 3D real environment [12]. AR applications in education have demonstrated significant value and advantages [15,16].…”
Section: Augmented Realitymentioning
confidence: 99%
“…Regarding AR, no study found a negative effect on CL, 3 reported no effect (27%) and 4 (36%) a positive effect of this type of imT on learners' CL (Figure 5.b). In their respective RCT studies on 70 students, Kucuk et al (2016) and Lee & Hsu (2021) found a positive effect on CL (decrease in self-reported overall CL) when using mAR rather than traditional media (pictures and text) or e-books. They also showed an improvement in learning neuroanatomy and makeup design.…”
Section: Descriptive Resultsmentioning
confidence: 96%
“…Two of them showed that the use of AR allows a more adapted CL and a better learning of Makeup design or electronics laboratory skills compared to less immersive media (e-books or manuals), but that there was no effect on motivation (Lee & Hsu, 2021;Singh et al, 2019). In a similar vein, one paper showed that VR, for teaching historical facts, had a negative effect on CL, and that this technology led to poorer learning than video media, while motivation did not change between conditions (Parong & Mayer, 2021b).…”
Section: Rq3 -What Are Links Between Cognitive Load and Curiosity Sta...mentioning
confidence: 99%
“…Games using mobile technologies are complex mechanisms that create multifaceted relationships among players. The potential of LBMGs (location-based mobile games) can be explored in informal education settings [1,2] while addressing wide and diverse fields of research such as mobile learning (m-learning), situated learning, and gamebased learning [3]. According to Schito et al [4], LBMGs provide teachers with methods of conceptualizing classes with long-term learning impact, through ludic, flexible, and innovative approaches.…”
Section: Introductionmentioning
confidence: 99%